Paper No 11.1: Enhanced Pixel Technology for Holographic Projection Displays. (September 2013) - Wilkinson, T. D.; Chen, R.; Butt, H.
Abstract: Holography is one of the best ways of making a truly 3D display, but there are limitations due to the hologram technology such as the traditional LCD square pixel. We explore other possibilities based around nanotechnology, which allow submicron pixel pitches and break the restrictions of pixel boundaries and geometries.